Effects of Organic and Inorganic fertilizers on the Growth of Juvenile Oreochromis Shiranus - Matsimbe, M; Kapute, F (Effects of Organic and Inorganic fertilizers on the Growth of Juvenile Oreochromis Shiranus, 2011)
The experiment to investigate the effects of organic and inorganic fertilizers on primary production and growth of Oreochromis shiranus was conducted in fifteen 3m2 concrete tanks at the Aquaculture Fish Farm, Bunda College, University of Malawi. Fish with mean weight of 8 ± 1g were stocked at 30fish/m2. There were five treatments (inorganic and feed, inorganic only, chicken manure and feed, chicken manure only, and feed only) which were replicated three times. After 84 days, fish raised on chicken manure and feed were significantly (P<0.05) larger and had higher net annual yields than the rest of the treatments. For treatments with either feed and fertilizer only, organic fertilizer had the highest fish growth rate and primary production. Significantly (P<0.05) higher amounts of chlorophyll a were produced in tanks fertilized with chicken manure. Overall, results obtained in this study, suggest that the use of chicken manure only, chicken manure and feed combination produces better results than inorganic fertilizer with either feed or no feed combination.
Keywords: Fertilization, organic fertilizer, inorganic fertilizer, Oreochromis shiranus, chlorophyll